Biointensive Integrated Pest Management in Horticultural Ecosystems - Reddy, P. Parvatha; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
Through ‘Green Revolution’ in late 1960s, India achieved self-sufficiency in food production, but still the country has not achieved self-sufficiency in production of horticultural crops. Most of the growth in food production during the green revolution period is attributed to the use of higher levels of fertilizers and pesticides which are continuing to destroy stable traditional ecosystems. The challenge before the crop protection scientist is to increase yields from the existing land without harming the environment and resource base. This can be achieved by adopting eco-friendly Biointensive Integrated Pest Management (BIPM) strategy. BIPM incorporates ecological and economic factors into agricultural system design and decision making, and addresses public concerns about environmental quality and food safety. The benefits of implementing BIPM can include reduced chemical input costs, reduced on-farm and off-farm environmental impacts, and more effective and sustainable pest management. An ecology-based IPM has the potential of decreasing inputs of fuel, machinery, and synthetic chemicals-all of which are energy intensive and increasingly costly in terms of financial and environmental impact. Such reductions will benefit the grower and society. The present book deals with the most recent biointensive integrated approaches for pest management utilizing components such as bioagents [predators, parasitoids and pathogens (bacteria, fungi, viruses)], botanicals (biofumigation, oil cakes, FYM, compost, crop residues, green manuring and other organic amendments), arbuscular mycorrhizal fungi, physical methods (hot water treatment of planting material, soil solarization), cultural methods (crop rotation, summer ploughing, fallowing, intercropping, pruning, mulching, spacing, planting date, trap cropping, etc.), biorational chemicals (pheromones) and resistant cultivars. This book can serve as a useful reference to policy makers, research and extension workers, practicing farmers and students. The material can also be used for teaching post-graduate courses.
Section I Introduction -- 1. Introduction -- Section II Fruit Crops -- 2. Tropical Fruit Crops -- 3. Sub-tropical Fruit Crops -- 4. Temperate Fruit Crops -- 5. Semi-arid Fruit Crops -- Section III Vegetable Crops -- 6. Solanaceous Vegetable Crops -- 7. Bulbous Vegetable Crops -- 8. Cruciferous Vegetable Crops -- 9. Malvaceous Vegetable Crops -- 10. Root Vegetable Crops -- 11. Leguminous Vegetable Crops -- 12. Cucurbitaceous Vegetable Crops -- 13. Leafy Vegetable Crops -- Section IV Ornamental, Medicinal, Aromatic and Tuber Crops -- 14. Ornamental Crops -- 15. Medicinal Plants -- 16. Aromatic Crops -- 17. Tuber Crops -- Section V Plantation and Spice Crops -- 18. Plantation Crops -- 19. Spice Crops -- Section VI Transfer of Crop Protection Technology and Conclusions -- 20. Transfer of Crop Protection Technology and Conclusions -- References.- Subject Index.
Keywords: Plant science; Botany; Agriculture; Entomology; Plant pathology; Plant ecology; Plant Sciences; Agriculture; Entomology; Plant Pathology; Plant Ecology